Genre- Based Approach to Teaching Writing - Ding, Eng Na (INTI International University, 2007)
This paper considers the application of genre-based approach to teaching of writing in the English for Specific Purpose (ESP) context, especially for learners aiming to use English in the professional setting. The genre-based approach to language teaching attempts to teach learners the ‘moves’ of a genre and to raise awareness of the linguistic features associated with the moves as a way to overcome learners’ difficulties in writing appropriately and effectively. This paper addresses the concern to help learners to make their choices in deciding what kind of information should be put in their writing to create meaningful and purposeful texts. A number of genre analysis strategies are presented to demonstrate how leaners can be taught to modify and blend their choices of words according to the contexts in which they write. 65 Business majors participated in this study. The control group (N=31) were taught through the usual lecturing style while the experimental group (N=34) were taught using the genre-based approach. Following the multiple trait scoring of the learners’ texts, the texts were analyzed for content, structure and language while the moves were analyzed using the moves score. The results of the study indicate that learners do write better when they are made aware of the rhetoric structure and providing models seem to increase the salience of the communicative moves considered by the learners for inclusion in their texts.